Front cover: Protein kinase G signaling in cardiac pathophysiology: Impact of proteomics on clinical trials. Issue 5 (March 2016) - Kirk, Jonathan A.; Holewinski, Ronald J.; Crowgey, Erin L.; Van Eyk, Jennifer E.
Abstract : DOI:10.1002/pmic.201500401 There has been tremendous interest in identifying therapeutic interventions in cyclic guanosine monophosphate/protein kinase G (cGMP/PKG) signaling, based on the protective benefits derived from its targets. However, the signaling is very complicated, making clinical translation challenging. New proteomics techniques, primarily mass spectrometry‐based, allow us to explore these intricacies in never before seen detail. For details, see the review by Jonathan A. Kirk et al., pages 894–905. (Background image used with permission of Patrick J. Lynch, medical illustrator; C. Carl Jaffe, MD, cardiologist, ©2006, under the CC‐BY 2.5 license).